Prognostic Value of Liver and Spleen Stiffness in Patients with Fontan Associated Liver Disease (FALD): A Case Series with Histopathologic Comparison - Padalino, Massimo A. (J Cardiovasc Dev Dis, 2021)
The Fontan operation is the current surgical procedure to treat single-ventricle congenital heart disease, by splitting the systemic and pulmonary circulations and thus permitting lifespan to adulthood for the majority of newborns. However, emerging data are showing that Fontan-associated liver disease (FALD) is an increasing related cause of morbidity and mortality in patients with the Fontan circuit. We described the clinical, laboratory, and transient elastography (TE) findings in a case series of adults with the Fontan circuit, and also correlated data with post-mortem histological features, aimed to define the prognostic value of TE in the staging of FALD. All patients presented signs of a long-standing Fontan failure, characterized by reoperation need, systemic ventricle dysfunction, and FALD stigmata (liver and spleen enlargement, portal vein and inferior vena cava dilation, and abnormal liver function tests). Liver and spleen stiffness (LS and SS) values were indicative of significant liver fibrosis/cirrhosis and the presence of suggestive portal hypertension (LS mean 35.9; range 27.3–44.7 kPa; SS mean 42.1, range 32.2–54.5 kPa). Post-mortem evaluations confirmed a gross hepatic architecture distortion in all cases. All patients died from severe complications related to liver dysfunction and bleeding. TE correlated well with pathological findings and FALD severity. We propose this validated and harmless technique to monitor liver fibrosis extension and portal hypertension over time in Fontan patients, and to identify the optimal timing for surgical reoperations or orthotopic-heart transplantation (OHT), avoiding a higher risk of morbidity and mortality in cases with severe FALD.